A shared commercial legal heritage - reflections on commercial law reform in former British Colonies and Dependencies - McKenzie, Peter (Victoria University of Wellington Law Review, 2008)
This article reflects on Professor Tony Angelo's contributions to the laws of various British colonies, particularly Mauritius. The author illustrates different types of jurisdiction by reference to individual countries. First, the author discusses colonies with a received legal heritage – Mauritius, who has influences from its French colonial administration and English law, and Botswana who has hints of English commercial statutes. Secondly, the author discusses colonies with an underlying common law system – Uganda, Sierra Leone, and Samoa. None of these nations were settled colonies, but colonial administrators took with them a common law structure for contracts, and civil and commercial obligations, while retaining customary law and practices in relation to land. Finally, the Maldives is discussed as a "special case". The author then discusses his reflections on the colonial legal legacy, including the impact of the English language, the shared nature of the colonies' legal systems (including a common accounting and business framework), and the "colonial legal patchwork". The author hopes that the impetus given by Professor Angelo to law reform in Mauritius, as well as other nations, will continue.